Social customer relationship management application of MSMES the crisis environment - Sathana, V. (University of Jaffna, 2024)
Purpose: Sri Lanka has been under the pressure due continuous crisis environment since 2019. Especially the micro producers have been facing huge problem to market their products. Interaction of higher number of intermediaries create high cost; at last retailers impose high prices for the products. Especially, Sri Lanka has been facing political crisis which creates the situation of severe shortage of food, electricity, fuel, and medicine, inflation, reducing currency value etc. This situation demolishes the dream of growth and prospectus of MSME startups. The purpose of this research is to find out the best ways to apply the Social Customer Relationship Management (SCRM) for the success of SME sector in Sri Lanka. Design/Methodology/Approach: This study is built up based on the qualitative research. Researcher selected Food based manufacturing sector to do the research. Purposive sampling technique was applied to select the respondents for this study. Data were collected through the focused group discussion with the three groups, from namely, owners of the MSMEs, Government officers and academics and students from Universities in Northern Province. Findings: The researcher developed a SCRM model for the micro producers on the university and faculty platform. The model includes five components, such as Data Base-Micro food producers, Government Institutions and departments, University, Data base- Consumer and Social media platforms- Supply Schedule and Demand schedule. Research limitations: This SCRM model needs to be empirically tested for micro producers. Implications: It will provide market opportunity with reasonable prices and profits. The university will take social responsibility to engage in the community development activities. This model suggests to government institution to collaborate with university to serve for the SME sector. This model needs to be applied in all universities and encourage them to work for MSME sector as their corporate social responsibility activity.
Keywords: Social customer relationship management; MSMEs; Social media